Acquired factor XIII deficiency: a therapeutic challenge - Boehlen, Françoise; Casini, Alessandro; Chizzolini, Carlo; Mansouri, Behrouz; Kohler, Hans Peter; Schroeder, Verena; Reber, Guido; Moerloose, Philippe de (Thrombosis and Haemostasis, 2013)
Less than 60 cases of acquired factor (F)XIII deficiencies have been reported, most having distinct clinical features. To illustrate the therapeutic challenges of acquired FXIII inhibitors, we report a case of a 65-year-old patient with no previous bleeding history who suddenly developed massive haemorrhages associated to a strong and isolated FXIII inhibitor. No underlying disorder has been detected till now after three years of follow-up. Despite aggressive treatment with prednisone, rituximab, cyclophosphamide, immunoglobulin, immunoadsorption and immune tolerance his inhibitor is still present, although at low titre and with a clinical benefit since the patient has no more bleed since more than one year. Moreover the patient had a venous thromboembolic complication. After a review of the management of acquired FXIII deficiency patients and based on the management of acquired haemophilia we discuss a possible strategy for such difficult cases.
Keywords: Acquired factor XIII deficiency; factor XIII concentrates; thrombosis; immunosuppression; Fibrogammin P®